2017
DOI: 10.14260/jemds/2017/634
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Clinical Profile and Outcome of Patients With Acute Respiratory Distress Syndrome in a Tertiary Care Hospital in North East India

Abstract: BACKGROUND Acute respiratory distress syndrome (ARDS) is a life threatening condition in which respiratory failure occurs due to lung injury caused by various aetiological factors. Acute hypoxemic respiratory failure as occurs in ARDS requires positive pressure ventilation. ARDS is a major cause of morbidity and mortality; and it also leads to major expenditure in intensive care units. MATERIALS AND METHODS This is a prospective observational study conducted over a period of one year in Emergency/ICU to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Moreover, ARDS has been linked to clinical features such as severe dyspnea, tachypnea and hypoxemia according to [49]. Other studies on the clinical profile of ARDS had shown that it is associated with breathlessness, hypotension, tachypnea [50] and tachycardia [51]. Although, there are no clear clinical features for ARDS, it is evident that ARDS is linked to cardiorespiratory and cardiovascular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ARDS has been linked to clinical features such as severe dyspnea, tachypnea and hypoxemia according to [49]. Other studies on the clinical profile of ARDS had shown that it is associated with breathlessness, hypotension, tachypnea [50] and tachycardia [51]. Although, there are no clear clinical features for ARDS, it is evident that ARDS is linked to cardiorespiratory and cardiovascular mechanisms.…”
Section: Discussionmentioning
confidence: 99%